Ventura (2020)
Ventura is a digital venture that offers a service of celebrations traveling around Bogotá, led by local experts, where beyond going to enjoy the charm and variety of experiences, visitors can contribute in a sustainable way to the implementation of solutions that benefit the visited destination, providing ideas and inputs from their personal experience, knowledge and professional skills in favor of improving the productive chain of farmers. Our company is aimed at altruistic people with a high spirit of service to the community, who are fascinated to know new and authentic places, the customs and ways of life of the locals, live a cultural experience different from the city where they reside, get involved in the way of life of the peasant and that they like to learn while having fun. We are a company committed to the economic and socio-cultural development of the communities, focusing all our activities in favor of the environment...